Die Indigenenbewegung in Ecuador : Diskurs und Dekolonialität - Altmann, Philipp (Global Studies, 2013)
The Indigenous Peoples Movement, despite its enormous diversity, is an important social player in Ecuadorian Society. Since the transitional period between the mid-1970s and mid-1980s, it has established a discourse which combines identity with class position and is structured around the political terms Indigenous sovereignty, nationality, territoriality, plural nationality, interculturality, and "the good life". Philipp Altmann shows how this discourse stands in opposition to the colonial structuring of society and its effects - such as discrimination and inequality - and is therefore to be understood as decolonial.